2014
DOI: 10.1097/sla.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

A Noise-Reduction Program in a Pediatric Operation Theatre Is Associated With Surgeon's Benefits and a Reduced Rate of Complications

Abstract: Spontaneous noise during pediatric operations attains the magnitude of a lawn mower and peaks resemble a passing truck. The sound intensity could be reduced by 50% by specific measures. This reduction was associated with a significantly lowered number of postoperative complications. The surgeon's benefits are idiosyncratic with "responders" experiencing marked improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
90
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 24 publications
1
90
0
4
Order By: Relevance
“…While typical OR sound levels can range from 62 to 72 dBA, 28 Engelmann et al 19 showed in a nonrandomized, prospective study that decreasing noise levels from 63 to 59 dBA in a pediatric surgical suite was associated with improvement in team communication and a decrease in postoperative complication rate. We previously demonstrated in a randomized, controlled, simulation-based experiment that exposure to typical OR background noise is associated with increased perception of fatigue and task load levels by anesthesia residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While typical OR sound levels can range from 62 to 72 dBA, 28 Engelmann et al 19 showed in a nonrandomized, prospective study that decreasing noise levels from 63 to 59 dBA in a pediatric surgical suite was associated with improvement in team communication and a decrease in postoperative complication rate. We previously demonstrated in a randomized, controlled, simulation-based experiment that exposure to typical OR background noise is associated with increased perception of fatigue and task load levels by anesthesia residents.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased sound levels were associated with fewer postoperative surgical complications. 19 As part of the intervention, landline phone ringers were muted, cell phones and any personal conversations were banned during procedures, medical and equipment alarm volumes were decreased, and doors were kept closed with entry and exit activity prevented. Many of these draconian measures may not be practical in all surgical environments.…”
mentioning
confidence: 99%
“…Increased noise levels in any workplace, including an OR, have been found to contribute to miscommunication . To reach 90% accuracy of effective oral communication, a difference of 10‐15 dB(A) between the speaker's voice and the ambient noise levels must be achieved .…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that noise levels within a workplace (which includes OR) do not exceed 55 decibels . We hypothesized that the noise levels in our OR would surpass these recommendations.…”
Section: Introductionmentioning
confidence: 97%
“…And although the noise pollution problem in OR is inarguable, very little has been invested to find and develop solutions. Engelmann et al showed a significant positive effect with lower rate of OR surgical complications by implementing consequent noise hygiene in the OR: no phones, a ban on non-essential speaking, reduction of alarm sounds of monitor equipment to the minimum and displacement of loud machines as far as possible 18. Of course, the use of earplugs can reduce noise, even in the OR, but their use also significantly reduces necessary communication.…”
Section: Introductionmentioning
confidence: 99%